TRANSPARENCY OBLIGATIONS OF THE MUNICIPALITIES OF SONORA. DEGREE OF COMPLIANCE AND SANCTIONS TO PUBLIC SERVANTS - Morales Tostado, María del Carmen (UNIVERSIDAD DE SONORA, 2023)
The existence of the corruption phenomenon in Mexico is undeniable and has negative consequences for all citizens, as a strategy to prevent acts of corruption arises Transparency and Access to Public Information. As legal support, in 2022 the first Transparency Law is approved and subsequently its state approval. However, the corruption perception index published in 2002 places Mexico in 124th place out of 180 countries. In conducting this research, laws, books, articles, transparency portals and other information of the municipalities under study were reviewed, and a qualitative approach was chosen.  The objective of the investigation is to analyze the Information Transparency Obligations of the Municipalities of Sonora, to identify the degree of non-compliance and the sanctions of public servants. Among the findings, it can be pointed out that progress has been made in the legal framework, to give certainty to the citizen to have access to the information they require about the government's activities. The sanctions imposed at the municipal level in the State of Sonora are analyzed, which is made up of 72 municipalities, of which 16 obtained a total compliance of 100 points, 49 municipalities partially complied, and 9 municipalities showed total non-compliance Keywords: Transparency obligations, Compliance and Sanctions